Challenges in Teaching English Majoring Spa Therapist at Berlian Salon and Spa - Rahman, Lalu Isnaeni (Lembaga Yasin AlSys, 2022)
This study was conducted to ascertain the challenges encountered by English teachers in Berlian Salon and Spa. One of the job training institutions in Central Lombok is Berlian Salon and Spa where this institution has been established since 2016 until now. This institution has several majors, including hospitality and spa therapist, which are currently the most popular majors. The institution always gets grants from the government to train underprivileged people to become entrepreneurs in the field of spa therapists. There are numerous challenges in learning English in Institution. The difficulties encountered were related to the status of the curriculum for English learning in institution, the students’ competency, and the students’ motivation regarding to the socioeconomic status of students and the family. Case study designs was chosen to help academics investigate, explain, characterize, assess, and speculate about complicated situations in context by answering a variety of questions about why, what, and how they happen. In -depth understanding of behaviors, processes, practices, and relationships in context can be gained through outcomes. Observation and interview were the instruments used by the researcher to collect the data.